Application of Industrial Engineering Technique for Better Productivity in Garment Industry - Viet Tinh, Nguyen; Husain, Syed Tam; Van Thanh, Nguyen (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
In recent years, with the strong development of the industry, it has created a competitive market. To be able to stand and survive requires businesses to create their own charisma based on the products they create must have the quality, cost and speed quickly. To do that requires businesses to have proper production strategies. Especially for the garment industry, which has a lot of waste in the production process that needs to be eliminated. This study focuses on the construction of standard time sets and standard activities to help eliminate wasted time on hand movements and time spent by workers. The result ca be used to develop the standard operation procedures of the production process.